Co-existence of pancytopenia, autoimmune hemolytic anemia and hepatic dysfunction in intensive care unit patient: Graves’ disease - Mustafa Murat Midik; Şükriye Miray Kılınçer Bozgül; Banu Sarer Yürekli; Devrim Bozkurt (Ege Tıp Dergisi, 2026)
Graves' disease (GD) may rarely present with hematologic findings and hepatic dysfunction. Diagnosis may be difficult, but early diagnosis is important to avoid delays in treatment. According to a recent literature review, the association of pancytopenia, autoimmune hemolytic anemia (AIHA) and hepatic dysfunction in GD has not been reported before. We report the case of a 57-year-old woman admitted to the intensive care unit with symptoms of heart failure and diagnosed as GD with pancytopenia, AIHA and impaired liver function tests. Corticosteroid and anti-thyroid treatment was initiated and clinical and laboratory findings improved within the first week. Pancytopenia, AIHA and hepatic dysfunction may occur as the first manifestation of the disease or may be seen in the course of Graves' disease. The occurrence of these severe findings is very rare and respond well to treatment.